Phylogeography of the pelagic fish Seriola lalandi at different scales: confirmation of inter-ocean population structure and evaluation of southern African genetic diversity. Issue 4 (2nd December 2016) - Swart, BL; Bester-van der Merwe, AE; Kerwath, SE; Roodt-Wilding, R
Abstract : The study investigated the global and regional phylogeography of the yellowtail kingfish Seriola lalandi by examining genetic diversity and population genetic structure of this species at inter-and intra-ocean level and on a regional scale. DNA fragments of two mitochondrial genes, cytochrome b (Cytb) and cytochrome c oxidase subunit I (COI) and one nuclear gene, recombination activating gene 1 (RAG1), were sequenced to investigate the global-scale phylogeography of this species. The population genetic structure within the South Pacific, as well as along the South African coastline, was examined further using six microsatellite markers. Three distinct clades were identified for S. lalandi, which correspond with previously described subspecies of the North-East Pacific, North-West Pacific and the Southern Hemisphere. Within the latter, additional divergence was observed between the South Pacific and the South-East Atlantic regions. Divergence estimates were indicative of a Pacific origin for S. lalandi populations, because of Pleistocene vicariant events. Microsatellite analyses revealed overall significant genetic differentiation between South African and South Pacific samples. This corroborates recent findings on the global phylogeography of the species. No population differentiation was observed within South Africa, indicating high levels of gene flow.